Piroplasmid infection is not associated with clinicopathological and laboratory abnormalities in cats from Midwestern Brazil - de Oliveira, Camila Manoel; Yang, Sharon; Duarte, Matheus Almeida; Figueiredo, Daniela Maciel; do Rosario Batista, Liliane Maria; Marr, Henry; McManus, Concepta Margaret; André, Marcos Rogério [UNESP]; Birkenheuer, Adam Joseph; Paludo, Giane Regina (Springer Nature, 2022)
Feline piroplasmids include the genera Babesia spp., Cytauxzoon spp., and Theileria spp. In Brazil, there are few reports regarding these hemoprotozoans; however, clinicopathological and molecular data are scarce. This study aimed to characterize the clinical relevance of these parasites through hematological, biochemical, and molecular approaches. For this purpose, 166 cats from Brasilia, Federal District, Midwestern Brazil, were screened using a quantitative polymerase chain reaction (qPCR) for piroplasmids based on the LSU4 mitochondrial gene, which resulted in an overall prevalence of 36/166 (21.7%). Twelve of 166 samples (7.2%) were positive for C. felis, while 19/166 (11.4%) were positive for Babesia vogeli. No samples tested positive for Theileria spp. Babesia vogeli and Cytauxzoon spp. LSU4 sequences showed identities of 97–100% and 99.3%, respectively, to US isolates. The hematological and biochemical findings did not differ significantly between the cats that tested positive and negative for piroplasmids. Although the lack of abnormalities in clinical and laboratory parameters does not eliminate the possibility that these cats were sick and recovered, it may suggest that the Brazilian strain of Cytauxzoon spp. is not as pathogenic as that from the USA, despite the high molecular identity with North American isolates.
Keywords: Babesia vogeli; Biochemistry; Cytauxzoon spp; Feline; Hematology; Piroplasmida